The Evaluation of In-Hospital Transportation of Emergency Room Critically Ill Patients - Turan Tahirli; Sercan Yalçınlı; Yusuf Ali Altuncı (Genel Tıp Dergisi)
Backround/Aims:The overcrowding of emergency departments, insufficient bed capacity in these units, lack of integrated radiology units, and the distance of other departments and intensive care units from the emergency department make it inevitable to transport patients within the hospital for either short-term or long-term purposes. Patients can be transported at least once for diagnostic and treatment procedures to radiology units, operating rooms, or intensive care units for admission. However, even during short-term patient transport in critical situations, complications may arise. Methods:This study evaluates the data obtained prospectively by examining the transport information of 588 patients who met the study criteria in an eight-month period in the emergency department of a university hospital in 2020. The study is designed to assess survival, disability, and the safe transport process of critically ill patients transported from the emergency department to hospital imaging, interventional procedures, surgery, and admission units. For statistical analysis of the data, independent sample t-test was used for normally distributed variables, Mann-Whitney U test when the normality assumption was not met, chi-square, ANOVA tests for the comparison of categorical variables. The significance level for all hypothesis tests was set at 0.05. Results:Of the 588 patients included in the study, 36.9% were female and 63.1% were male, with an average age of 61.9 years. The average transport time for patients transferred for examination, admission, or interventional procedures was 18.5 minutes. 63.3% of the transferred patients sought medical attention during the night shift. During transport, 51.7% of patients experienced problems. Among the issues encountered during transport, 48.3% were related to the system, 27% were related to equipment, and 24.7% were related to human factors. The most common problem, accounting for 23.0%, was waiting in radiology units or corridors for radiology examinations and interventional procedures. Conclusion:In critically ill patients in the emergency department, the most common transport problems occur when planned examinations take place outside the emergency department. Therefore, the necessity of these requests should be carefully evaluated to reduce complications that may occur during transfer. The physical organization of emergency departments should be designed to facilitate the transfer of critical patients as quickly as possible to prevent problems that arise due to prolonged transfer times.